Phytochemical Profile and Antimicrobial Effects of Different Medicinal Plant: Current Knowledge and Future Perspectives - Mulat, Mulugeta; Khan, Fazlurrahman; Muluneh, Gizachew; Pandita, Archana (Current Traditional Medicine, 2020)
The application of medicinal plants for combating various human ailments, as a food fortificant and additive have been adapted from ancient routine custom. Currently, developing countries use plants as a major source of primary health care. Besides, the emerging drug resistant pathogenic microbes encourage the utilization of medicinal plants as preeminent alternative sources of new bioactive substances. Extensive research findings have been reported in the last three decades. But methods to investigate the phytoconstituent and their biological effects are limited. This review contains brief explanations about the selection of medicinal plants, procedure for obtaining the crude as well as essential oil extracts, phytochemical screening, and in-vitro evaluation of antimicrobial activity. Furthermore, the antimicrobial activity of medicinal plant extracts reported from their respective solvent fractionated and non-fractionated in-vitro analysis has also been described in the present paper. The bioactive substances from medicinal plant along with chemical structure and biological effects are highlighted in the content.
Keywords: phytochemicals